Social Workers during COVID-19: Do Coping Strategies Differentially Mediate the Relationship between Job Demand and Psychological Distress? - Ben-Ezra, Menachem (Br J Soc Work, 2020)
The consequences of the coronavirus disease of 2019 (COVID-19) pandemic have raised many challenges in the social services workforce. The current study aimed to examine the associations between job demands, coping strategies (i.e. emotion-focused coping and problem-focused coping) and psychological distress exhibited by social workers during the COVID-19 pandemic. In addition, the mediating role of different coping strategies was investigated for the associations revealed. The participants were 615 social workers, working in various organisations and with diverse populations in Israel. Each completed a validated self-report questionnaire. Results revealed that job demands were significantly associated with higher psychological distress, and that coping strategies, especially emotion-focused coping was associated with higher psychological distress and with job demands. In addition, emotion-focused coping strategies were found to mediate the association between job demands and psychological distress, especially ventilation of emotion beyond other strategies, which relate to emotion-focused coping. These findings are discussed with relation to a stress and coping theory, suggesting that in social work practice there is a need for intervention measures to improve social workers’ coping strategies during crises such as the COVID-19 pandemic.